Hubungan antara Kebiasaan Sarapan dan Status Gizi dengan Kejadian Anemia pada Remaja di Kawasan Bantaran Kali Winongo Kota Yogyakarta - Mudita Sri Hidayah (STIKes Surya Global Yogyakarta, 2022)
Background: Nutritional anemia is one of Indinesia’s major public health problems. Anemia in adolescent girls contributes to maternal and foetal mortality and morbidity in future. The purpose of this study is to determine the prevalence of anemia among adolescent in a slum area Kali Winongio and and to determine the influence of breakfast habbits and body mass index (BMI) associated with it.Methods: A community-based cross-sectional study was conducted among 62 adolescent in a slum area at Kali Winongo Yogyakarta from September to December 2019. Information regarding socio-demographic and breakfast habits was recorded in pre-designed. Hemoglobin estimation was done by HemoCue system. Data was analized by mean, deviation standard and chi-square test.Results: The percentage of anemia in adolescents was 29.03%. The greatest distribution of anemia incidence between 10-14 years age group. Most of them have a breakfast habit, which was 88.4%. Bivariate analysis showed that there was no significant relationship between gender, age (p = 0.14), nutritional status (p = 0.85), and breakfast habits (p = 0.93) with the incidence of anemia.Conclusion: there is no relationship between breakfast habits and nutritional status with the incidence of anemia. Breakfast not only needs to be familiarized but also needs to be considered the menu at breakfast.Keywords: anemia, breakfast habits, nutritional status